Media Penselo Berbantuan LKS untuk Memfasilitasi Pembentukan Konsep Matematis Siswa SMK pada Materi Logaritma - Ciptianingsari Ayu Vitantri; Ririn Ulfi Ardiyanti (Institut Agama Islam Negeri (IAIN) Tulungagung, 2021)
Logarithms are classified as new material for vocational students, where this material has never been taught in previous levels of education. A media in logarithmic learning are needed so that concept formation can be well received by students. This study aims to determine the validity and effectiveness of penselo media assisted by worksheet in facilitating the formation of students' logarithmic concepts. This is a development research with instruments used in this study are worksheet, media validation sheets, student response questionnaire, and field notes. Grade X students of SMK Telekomunikasi Darul Ulum are the test subjects in this study. The data in this study consisted of quantitative data and qualitative data. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using the stages of data reduction, data presentation and conclusion drawing. The results of the validation test on aspects of manual tools were 87.5%, language aspects were 75%, content aspects were 81.25% and other aspects were 81.25%, while student responses were 3.54 which met the very good category. It can be concluded that the penselo media assisted by worksheet is valid and effective in forming the initial concept of logarithm.